Investigação da origem biossintética de cromenos e cromanos em Piper aduncum e Peperomia obtusifolia (Piperaceae) - Souza Júnior, Amauri Alves de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Chromanes and chromenes are secondary metabolites commonly found in species of the genera Piper and Peperomia, belonging to the Piperaceae family. They are characterized by the presence of a benzopyran core showing a benzene ring fused to a pyran ring. This class of compounds is pharmacologically important, since they from shown a broad range of biological activities including antifungal, trypanocidal, antioxidant and anti-parasitic. The benzopyrans isolated from Piper and Peperomia species showed diversity biosynthetic pathways, mainly related to the aromatic moieties. The biosynthesis of Piper species involve the shikimic pathway showing as the first precursor the p-hydroxybenzoic acid, whereas in Peperomia species would be operating the route of acetate. The present work aimed to study the biosynthetic relationship of benzopyrans present in Piper aduncum and Peperomia obtusifolia as well as to determine the metabolic dynamics involved in their formation related to metabolic and enzymatic levels, since the chromenes isolated from Piper aduncum describe well-defined circadian rhythm. Studies of circadian rhythm performed in Peperomia obtusifolia, aiming to follow the formation of chromane 3,4 -dihydro- 5 -hydroxy -2 ,7- dimethyl-8- (3-methyl -2- butenyl) -2 - (4 -methyl -1 ,3- pentadienyl )-2H -1- benzopyran carboxylic acid (4) from P. obtusifolia showed no uniform sigmoidal curve, common to the chromenes isolated from Piper aduncum. The accumulation of the chromane 4 showed a maximum at 18:00 pm, but others peaks of the same concentration were observed at 06:00 am and 15:00 pm, corroborating to establish a random pace. To evaluate the biosynthetic origin of the chromane 4, feeding experiments were conducted using a precursor enriched with stable isotopes (ethyl [2-13C ]-sodium acetate) in the leaves of P. obtusifolia. Experiments were performed using seedlings of P. obtusifolia. The enriched extracts...

Cromanos e cromenos são metabólitos secundários comumente encontrados em espécies dos gêneros Piper e Peperomia, pertencentes à família Piperaceae. São caracterizados pela presença de um núcleo benzopirânico (um anel benzeno fundido a um anel pirano). Essa classe de substâncias é importante do ponto de vista farmacológico, uma vez que apresenta vasta gama de atividades biológicas, incluindo antifúngica, tripanocida, antioxidante e antiparasitária. Os benzopiranos isolados de espécies de Piper e Peperomia apresentam diversidade quanto aos substituintes da unidade aromática de suas estruturas químicas. Baseado no exposto, rotas biossintéticas distintas foram propostas. Em espécies de Piper essas rotas envolveriam a via do ácido chiquímico pela atuação do ácido para-hidroxibenzóico, enquanto que em espécies de Peperomia estaria operando a via do acetato. O presente trabalho teve como objetivo estudar a relação biossintética dos benzopiranos presentes nas espécies Piper aduncum e Peperomia obtusifolia, bem como a determinação da dinâmica metabólica envolvida na formação dos mesmos, tanto em nível metabólico como enzimático, uma vez que os cromenos isolados de Piper aduncum descrevem ritmo circadiano bem determinado. Estudos de variação circadiana realizados em Peperomia obtusifolia com o objetivo de acompanhar a formação do cromano ácido 3,4-diidro-5-hidróxi-2,7-dimetil-8-(3-metil-2-butenil)-2-(4-metil-1,3-pentadienil)-2H-1-benzopirano carboxílico (4) não demonstraram ritmo uniforme, do tipo sigmoidal, comum aos cromenos isolados de P. aduncum. O acúmulo do cromano 4 mostrou um máximo às 18h00, mas outros picos de concentração do mesmo foram observados às 06h00 e 15h00 e corroboram para o estabelecimento de um ritmo aleatório. Para a avaliação da origem biossintética de 4, foram realizados experimentos de incorporação utilizando precursor enriquecido...
Keywords: Quimica organica; Biossintese; Espectrometria de massa; Metabólitos; Biosynthesis